MEDAN THE RELATIONSHIP OF EMOTIONAL QUOTIENT AND LEARNING INTEREST WITH LEARNING ACHIEVEMENT IN ISLAMIC EDUCATION AT SMA NEGERI 16 MEDAN - Syamsu Nahar; Wahyudin Nur Nasution; DTM Ayub Azhari (JURNAL TARBIYAH, 2020)
This study is a quantitative approach. The variables of this study consisted of the dependent variable and the independent variable. This study aims to determine the magnitude of the relationship between the dependent variable and the independent variable. This study applied correlational research. The population of this study consisted of all students of SMA Negeri 16 Medan, 900 students, in 2020. The sample of this study was set to be 100 students, and the sampling was done by using of Slovin technique. The techniques of data collection in this study were a Likert scale questionnaire and pre-test and post-test. The research instruments were arranged according to variable indicators based on the direction and guidance of the Thesis advisor, then tested on students of Medan 16 High School. All data collection instruments for the first independent variable consist of 40 items from the second independent variable, consisting of 40 items. The requirement test for the first independent variable data and the second independent variable used data normality test, comparable data, and linearity. Hypothesis testing uses the t-test to look for correlations on each variable and a partial correlation test with the product-moment formula or SPSS version 20. The results of the research hypothesis state that there is a positive and significant relationship between emotional quotient and learning interest with learning achievement in Islamic Religious Education subjects, with proven that r arithmetic> rtable and also t arithmetic> ttable that can be accepted with a decision-making level of 0.05.